Feasibility Analysis of Boba Beverage Business In Ambon City: Case Study Based on Porter's Five Forces - Mulyanto, Triadi; Hamizar, Arizal (Rangkiang: Journal of Islamic Economics and Business, 2024)
This study aims to analyze the feasibility of boba beverage business in Ambon City using the Five Forces Porter approach. The research method used is descriptive qualitative by collecting data through interviews, observations, and literature studies. The analysis is done using the concept of Five Porter Forces, namely the competition between existing competitors, supplier negotiation power, buyer negotiation power, the threat of new entrants, and the threat of substitute products. The results show that the boba beverage industry in Ambon City has a significant potential and is still growing. The competition between existing competitors is relatively high with several well-known brands in the market, but there is still an opportunity to develop through innovative products and proper promotion. Supplier negotiation power is also relatively high due to the need for specialized raw materials, but there are several alternative suppliers that can be utilized. Buyer negotiation power is quite low because boba drinks are considered a premium product with a relatively high price. The threat of new entrants is relatively low due to several entry barriers in this industry, such as high investment costs and the difficulty of obtaining high-quality raw materials. The threat of substitute products is relatively low because boba drinks have a unique taste and a fairly loyal customer base.